The influence of electrode geometry on depth indentation of the resistance spot welding in the joining of steel and magnesium sheets in the car body - A. Dehghani; M. Sedighi (Journal of Advanced Materials in Engineering)
Nowadays, there is a desire in various industries, especially in the automotive industry, to join dissimilar sheet metals in order to reduce weight. Resistance spot welding is often applied to join body parts and its strength and dimensions of the weld are important. In this research, the influence of the electrode geometry with a diameter of 20 and 50 mm on the indentation depth of the resistance welding spot in the joining of sheet steel and the magnesium alloy AZ31 was investigated. A tensile shear test was carried out to evaluate the strength of the weld. The results showed that the strength of the joint was 5000 N and the 50% reduction in indentation depth by the electrode with a geometry diameter of 50 mm with an average indentation depth of 0.6 mm on the magnesium side. The structure of the weld in this joint had three Braze, solid solution, and solder regions. Moreover, dendritic coaxial grains in the center and coaxial and columnar grains at the periphery of the spot weld were observed.